2013
DOI: 10.1155/2013/378264
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Contents and Antioxidant Potential of Crataegus Fruits Grown in Tunisia as Determined by DPPH, FRAP, and β‐Carotene/Linoleic Acid Assay

Abstract: Crataegusfruit is one of most important fruits in Tunisian flora. Some fruits of this genus are edible. This study was undertaken in order to examine the benefits of these fruits in human health and their composition of antioxidants including total polyphenol, flavonoids, proanthocyanidins content, and total anthocyanins. The antioxidative properties of the ultrasonic methanolic extract were assessed by different in vitro methods such as the FRAP, DPPH, andβ-carotene/linoleic acid assay. We concluded that peel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 19 publications
1
18
0
2
Order By: Relevance
“…Flavonoid compounds are considered to be the largest group of naturally occurring phenol and their antioxidant capacity are depending on the position of OH group [58]. Therefore, the antioxidant activity of plant extracts also comes from the presence of other antioxidant secondary metabolites, such as flavonoids, proanthocyanidins, anthocyanins, and not limited to phenolics content [59,60].…”
Section: Correlation Between Tpc Tfc and Antioxidant Capacity Of Samentioning
confidence: 99%
“…Flavonoid compounds are considered to be the largest group of naturally occurring phenol and their antioxidant capacity are depending on the position of OH group [58]. Therefore, the antioxidant activity of plant extracts also comes from the presence of other antioxidant secondary metabolites, such as flavonoids, proanthocyanidins, anthocyanins, and not limited to phenolics content [59,60].…”
Section: Correlation Between Tpc Tfc and Antioxidant Capacity Of Samentioning
confidence: 99%
“…In b-carotene/linoleic acid assay, there is discoloration of b-carotene in reaction with linoleic acid-free radical which was generated upon the increased temperature due to the removal of hydrogen atoms coupled in two double bonds of linoleic acid (Amarowicz et al 2004). This reaction leads the loss of conjugation which automatically affects the decrease in absorbance at 470 nm for b-carotene, and thus the antioxidants present in solution protect reduction of b-carotene through reacting with other free radicals or linoleate-free radical in reaction system (Mraihi et al 2013). In this study, we found a considerable variation in the antioxidant capacity measured with DPPH, FRAP, and b-carotene/linoleic acid antioxidant assays using different extractions methods for medicinal plants selected from the Unani system of medicine (Table 3).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…C. monogyna fruits are characterized by about 2.0 times higher concentration of total phenolics than yellow fruits of C. azarolus and about 5.0 times higher concentration of total flavonols (Mraihi et al 2013, Mraihi et al 2015. Total amount of total phenolics in peel of C. monogyna fruits collected in Tunisia is between 45.70 ÷ 123.35 mg GAE 100g -1 DW (Mraihi et al 2013). Pliszka et al (2016) obtained higher concentration of TPC with use of exraction with citric acid were (913.0 ± 41.8 mg GAE 100 -1 FW) compared with extraction with 80% methanol (602.7 ± 17.0 mg GAE 100g -1 FW) for C. monogyna fruits.…”
Section: Resultsmentioning
confidence: 90%
“…In fresh HF of Crataegus monogyna total phenols was determined at level of 62.00 mg 100g -1 FW (Leja et al 2007). C. monogyna fruits are characterized by about 2.0 times higher concentration of total phenolics than yellow fruits of C. azarolus and about 5.0 times higher concentration of total flavonols (Mraihi et al 2013, Mraihi et al 2015. Total amount of total phenolics in peel of C. monogyna fruits collected in Tunisia is between 45.70 ÷ 123.35 mg GAE 100g -1 DW (Mraihi et al 2013).…”
Section: Resultsmentioning
confidence: 96%